2005
DOI: 10.1021/es0491228
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Natural Attenuation via in Situ Reductive Dechlorination of Polychlorinated Biphenyls in Sediments of the Twelve Mile Creek Arm of Lake Hartwell, SC

Abstract: Polychlorinated biphenyl (PCB)-contaminated sediment cores taken from five locations in Lake Hartwell, SC, with an increasing distance from the point source were evaluated for the presence of in situ reductive dechlorination of PCBs on the basis of a comparative congener-specific analysis of PCB distribution profiles between historical (1987) and current (1998) sediments from the same sites. A layer of 1998 sediment that was equivalent to 1987 sediment was determined by direct comparison of total PCB depth pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 19 publications
4
48
0
1
Order By: Relevance
“…Microbial reductive dehalogenation of halogenated biphenyls as well as of other haloorganic compounds has been extensively studied using anaerobic sediment cultures and microcosms 17,23,28,33,74,78,94,100,101,130,134,137) . Most of the earlier reports provided little or no definitive information about dehalogenating microorganisms in the cultures in terms of quantity and quality.…”
Section: Pcb-dehalogenating Bacteria and Consortiamentioning
confidence: 99%
“…Microbial reductive dehalogenation of halogenated biphenyls as well as of other haloorganic compounds has been extensively studied using anaerobic sediment cultures and microcosms 17,23,28,33,74,78,94,100,101,130,134,137) . Most of the earlier reports provided little or no definitive information about dehalogenating microorganisms in the cultures in terms of quantity and quality.…”
Section: Pcb-dehalogenating Bacteria and Consortiamentioning
confidence: 99%
“…During dehalogenation process, the common electron donors include lactate, acetate and glucose (Rhee et al, 2003;Boyle et al, 1999). The metabolites are further degraded to non-toxic compounds by aerobic microorganisms (Bedard, 2003;Bedard et al, 2005;Boyle et al, 1999;Bzdusek et al, 2006a,b;Li et al, 2005Li et al, , 2012Magar et al, 2005a,b;Pakdeesusuk et al, 2005;Payne et al, 2013;Sanford et al, 1996;Yan et al, 2006). Dehalorespiration is critical for effective dehalogenation, and the effect of dissimilatory iron reduction on dehalogenation has been discussed (Li et al, 2008;Wu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Bioaugmentation of granular anaerobic methanogenic microbial consortium along with a suitable carbon source was successfully demonstrated (Nollet et al 2005). In this line, anaerobic dechlorination of PCBs has also been reported for various contaminated sites (Pakdeesusuk et al 2005). Macedo et al (2007) observed transformation of highly chlorinated PCB congeners as an effect of adaptation of microbial communities in contaminated soil.…”
Section: Bioaugmentation Of Anaerobic Organismsmentioning
confidence: 78%